Designing An Illustrated Book as An Educational Media Regarding Traditional Lampung Cakes to Increase Children's Interest in Local Products - Ajen Latamada, Puti; Moussadecq, Ade (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2024)
Lampung Province has a variety of traditional cakes, such as Selimpok, Sekubal, Engkak, Bangkit, Lapis Legit, Bebai Maghing and many others. However, some people prefer modern food such as bread in bakeries which are starting to emerge which are very popular with today's young generation, especially children, because of lifestyle factors. From data from interviews and questionnaires on children aged 6-12 years, they do not clearly understand the origins of regional cakes, the names of some regional cakes, and some have never tasted these regional cakes. Therefore, a media was designed in the form of a book illustrating Typical Lampung Traditional Cakes as a learning medium for children aged 6-12 years based on illustration work for education related to these traditional cakes, because children tend to like lots of pictures that add fun information, are easy to understand, and have interactive designs for children.